Assessment of Pulmonary Hypertension in Lung Transplantation Candidates: Correlation of Doppler Echocardiography With Right Heart Catheterization - AŞICIOĞLU, EBRU (ELSEVIER SCIENCE INC, 2016)
Background. Right heart catheterization (RHC) remains the gold standard to diagnosis of pulmonary hypertension among lung transplantation candidates. Doppler echocardiography (DE) may be as accurate as RHC, without risks of an invasive test. The aim of the study was to assess the feasibility of DE for the measurement of pulmonary artery pressure in lung transplantation candidates and the correlation between pulmonary artery pressures estimated by DE versus measured by RHC. Methods. A total of 103 lung transplantation candidates undergoing DE who were scheduled to undergo RHC within 72 hours were analyzed. The performance characteristics of DE were compared with RHC, and correlation analysis was performed to determine the correlation of pulmonary pressures obtained by DE versus measured by RHC. Results. The prevalence of pulmonary hypertension was 57% in lung transplantation candidates. Of the 103 candidates, evaluation of pulmonary artery systolic pressure (PASP) by DE was possible in 92 (89%). Median PASP by RHC was 45 (12-145) mm Hg and by DE 45 (20-144) mm Hg. There was a positive correlation between PASP estimated by DE and measured by RHC = 0.585, P < .0001). Sensitivity, specificity, and positive and negative predictive values of PASP estimation for diagnosis of pulmonary hypertension were 85%, 67%, 87%, and 61%, respectively. Conclusions. There is a strong positive correlation between PASP estimated by DE compared with measured by RHC with an acceptable sensitivity and specificity in detecting pulmonary hypertension. Echocardiography can be recommended for measuring pulmonary pressures in lung transplantation candidates.
Keywords: PRESSURE; ULTRASOUND